1997
DOI: 10.1002/hep.510260119
|View full text |Cite
|
Sign up to set email alerts
|

Association of a tumor necrosis factor promoter polymorphism with susceptibility to alcoholic steatohepatitis

Abstract: bility to ALD have thus far focused primarily on genes encod-SEE EDITORIAL ON PAGE 232 ing ethanol metabolizing enzymes. 3 Results have been conflicting, but it would appear that the known polymorphisms of genes encoding the alcohol and aldehyde dehydroTwin concordance studies suggest that genetic factors play genase enymes and the ethanol-inducible cytochrome P450, a role in determining why only a minority of heavy drinkers CYP2E1, play only a minor role in the Caucasian populadevelop hepatitis and cirrhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(96 citation statements)
references
References 9 publications
(17 reference statements)
5
87
1
3
Order By: Relevance
“…Oxidative stress from reactive lipid peroxidation, peroxisomal b-oxidation, and recruited inflammatory cells are the other potential explanations for elevated aminotransferase in insulin resistance. The insulinresistant state is also characterized by an increase in proinflammatory cytokines such as tumor necrosis factor-a (TNF-a), which may also contribute to hepatocellular injury (Grove et al, 1997). Thus, the observed increase in the activities of ALT, AST, and ALP in serum of diabetic rats may primarily be due to leakage of these enzymes from liver cytosol into bloodstream as a consequence of the hepatotoxic effect of STZ (El-Demerdash et al, 2005).…”
Section: Weight In Gramsmentioning
confidence: 99%
“…Oxidative stress from reactive lipid peroxidation, peroxisomal b-oxidation, and recruited inflammatory cells are the other potential explanations for elevated aminotransferase in insulin resistance. The insulinresistant state is also characterized by an increase in proinflammatory cytokines such as tumor necrosis factor-a (TNF-a), which may also contribute to hepatocellular injury (Grove et al, 1997). Thus, the observed increase in the activities of ALT, AST, and ALP in serum of diabetic rats may primarily be due to leakage of these enzymes from liver cytosol into bloodstream as a consequence of the hepatotoxic effect of STZ (El-Demerdash et al, 2005).…”
Section: Weight In Gramsmentioning
confidence: 99%
“…A number of single nucleotide polymorphisms (SNPs) in TNF-α promoter region have been identified, of which we chose to genotype TNF-α -857T/C and TNF-α -238G/A polymorphisms. It has been shown that the -857C and- 238A alleles cause an increase in TNF-α production (1314). The implication of these polymorphisms in susceptibility to several autoimmune diseases, such as rheumatoid arthritis, ankylosing spondylitis, and systemic lupus erythematosus, has been assessed (151617).…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased TNFα levels are found in patients with PBC [6], chronic viral hepatitis [7], fulminant hepatic failure [8], and negatively correlate with survival in patients with alcoholic liver disease [9]. In addition, TNFα levels are elevated in the serum of patients with alcoholic liver cirrhosis [10] and polymorphisms in the TNFα gene are associated with advanced fibrosis in alcoholic steatohepatitis [11]. Further, TNFα aggravates liver fibrosis induced by schistosomiasis in humans [12].…”
mentioning
confidence: 99%